Cyclooctynes as Building Blocks for the Synthesis of Arene-Annulated Eight-Membered Ring Systems - Große, Michel; Wegner, Hermann A. (Synlett, 2025)
Arene-annulated eight-membered carbocycles constitute a unique class of molecular architectures, combining the rigidity of aromatic ring systems with the distinctive conformational features of cyclooctene-derived frameworks. Among the various synthetic routes developed to prepare these structures, Diels–Alder reactions employing cyclooctyne derivatives as dienophiles stand out for their high degree of modularity as well as functional group tolerance. Herein, we provide an overview of these Diels–Alder-based strategies by comparing commonly employed strained alkyne dienophiles and classifying different types of diene systems. This systematic compilation of synthetic methods may help guide future developments in the synthesis of polycyclic structures containing eight-membered rings and foster their usage in functional materials and biological applications.
Keywords: Cycloaddition; Strained alkynes; Cyclooctyne; Diels–Alder reaction; Skeletal editing; Polycyclic aromatic hydrocarbons